Muscle injuries in 90 professional football players over 10 consecutive seasons: A comparison of two classification systems and their association with return-to-play time - Huber, P. J.; Schönnagel, B.; Dalos, D.; Frosch, K.-H.; Adam, G.; Welsch, G. H. (Scandinavian Journal of Medicine & Science in Sports, 2025)
The British Athletics Muscle Injury Classification (BAMIC) and the Munich consensus statement (MCS) are both commonly used classification systems and have been established in recent years to categorize muscle injuries and estimate return-to-play time (RTP). While the MCS classifies injuries based on clinical and radiological assessment, the BAMIC primarily relies on radiological imaging but also takes tendon involvement into account. However, there is no consensus on which classification is better suited for the assessment of acute muscle injury and its association with RTP. The aim of this study was to compare BAMIC and MCS in acute muscle injury of professional football players regarding RTP and to identify other player characteristics that influence the layoff time, given the fact that background approaches differ. In 90 professional football players, 169 MRI scans (3 Tesla) of acute muscle injuries were performed on average within 2.3 days of injury and assessed using the BAMIC and MCS. Grading of both classification systems was compared and correlated with RTP. Further player information, like recurrence of injury, dominant leg, affected side, age, or seasonal distribution, was evaluated. The grading of both classification systems correlated with RTP (BAMIC: r = 0.533, p < 0.001; MCS: r = 0.583, p < 0.001). Intratendinous injuries showed significantly longer layoff times (mean = 38.61 days, median = 26.5; range = 3-181; IQR = 25.3; CI = 20.2-38.5) compared to myofascial (mean = 14.17, median = 26.5; range = 3-181; IQR = 25.3; CI = 20.2-38.5) (p < 0.001) and myotendinous lesions (mean = 17.99, median = 26.5; range = 3-181; IQR = 25.3; CI = 20.2-38.5) (p = 0.002). The months of September (n = 22, 13.0%) and April (n = 20, 11.8%) showed significantly higher numbers of muscular injuries (p < 0.001). No association between the dominant side and affected side could be found (p = 0.476). Both classification systems provided a similar association with estimated RTP. The consideration of tendon injuries as classified in the BAMIC proves to be particularly important, as extended RTP can be expected. Still, usage might remain an individual choice. More emphasis should be placed on regeneration and prevention at the beginning and the end of the season to reduce the high incidences.